Studi Kelayakan Bisnis Pada Rumah Makan Saung Pojok Dadaha Kota Tasikmalaya - Azizah, Marwah; Sudono, Agus; Sukirman, Oman (Universitas Pendidikan Indonesia, 2016)
Saung Pojok Dadaha is a restaurant that operates since year 2009 and had afairly good development. Starting from small rice stalls and then evolved into arestaurant that is able to sell up to 1000 servings per day. The uniqueness of this Eating is House offer only one meal that is nasi timbel komplit that contains nasi timbel, ayam goreng serundeng, tempe goreng, tahu goreng, ikan asin, sambal, and lalapan at a price of Rp. 10.000,-. On his business trips, is currently going through a Saung Pojok Dadaha decline in sales quite significantly so that necessary to do study of business feasibility. The method used in this research is description verification with explanatory survey.Based on research results, obtained the results that the business of nasi timbelkomplit in Saung Pojok Dadaha deserves to be run and developed. Based on theanalysis of the financial aspects of investment appraisal indicator with using thecalculation of Net Present Value is explain this business feasible to be operate cause value of NPV is bigger than 0 (NPV0) or Rp. 1.691.405.357 Rp. 1.022.052.500. According to research result of non-financial aspect found several things that need to be evaluate, such as facility management, promotion, salary management, formation of management team, finance management in this case is about accounting, and completeness of licenses.